GIBRANISME: ANTARAEKSISTENSIALISME DAN ROMANTISISME - Fahruddin Faiz (UIN Sunan Kalijaga Yogyakarta, 2015)
Not many in this world there is a person as a philosopher as well as a poet. Among the few of them there is one popular name incontemporary literature's world, i.e. Kahlil Gibran. Many people knew Kahlil Gibran as poet-philosopher from Lebanon resided in Boston, United States. Gibran's thoughts and ideas are very philosophical and full of meaning, since expressed in beautiful poetical style, therefore popular in public. In another side, Gibran's styles are often using parables and aphorisms make people easier to understand even within esoteric and mystical dimension. Inits analysis the writer saw the whole Gibran 's vision and perception towards universal themes in life, including love, it could be said that Gibran is a person with sharp and clear view in perceiving reality around. Even to show the truth ofreality portrait, Gibran does not hesitate to break the common order and the